Substrate comparison for polypyrrole-graphene based high-performance flexible supercapacitors. (20th October 2020) - Bhargava, Priya; Liu, Wenwen; Pope, Michael; Tsui, Ting; Yu, Aiping
Highlights: Three substrates compared for the first time for flexible supercapacitor application. A novel polypyrrole-graphene-polypyrrole (PPy-rGO-PPy) coated on commercial conductive polyester fabric (Cu:Ni-PET) fabricated as flexible supercapacitor electrodes Cu:Ni-PET/PPy-rGO-PPy based device exhibited higher areal capacitance of 684 mF/cm 2 with 94.2% capacity retention after 4000 cycles than most polypyrrole composite based flexible supercapacitor electrodes reported in literature. Abstract: The high interest in wearable technologies has inspired an increased demand for portable, flexible energy storage devices. Currently, most commercial electrochemical energy storage units, such as supercapacitors, are available only in rigid formats, failing to meet the flexibility standards that allow their integration into wearables such as smart textiles and flexible electronics. To achieve flexibility, many research studies have separately reported different flexible substrates coated with active materials for flexible supercapacitor applications. However, there is a lack of studies comparing these substrates for their impact on the electrochemical performance of a supercapacitor cell, which can provide important reference and guidance for the design of flexible supercapacitors. To combat these limitations, we have compared the electrochemical performance of flexible supercapacitor constructed by three different commonly used substrates- commercially obtained conductive polyester fabric (Cu:Ni-PET), carbon cloth, and stainless-steel wire mesh (SSWM). Particularly, the effects of substrate properties such as conductivity, morphology, wettability on the electrochemical performance of the resulting polypyrrole-graphene-polypyrrole sandwich structure electrode are investigated in-depth. It is found that the best electrochemical performance is obtained for Cu:Ni-PET based device with a high areal capacitance of 684 mF/cm 2 at the current density of 2 mA/cm 2 and capacitance retention of 94.2% after 4000 cycles. The best electrochemical performance of Cu:Ni-PET based supercapacitors are mainly attributed to its high conductivity, good wettability, and unique surface morphology as well as excellent bendability. Graphical abstract: Image, graphical abstract